Preparation method of organic-inorganic hybrid phase change energy storage material

By using a combination of modified polyethylene glycol and active carrier in phase change energy storage materials, a double-layer clad structure of paraffin and modified chitosan is formed, which solves the problems of low energy storage density and poor circulation stability of existing phase change energy storage materials, and achieves higher energy storage density and thermal cycle stability.

CN118652668BActive Publication Date: 2025-03-04INSTITUTE OF APPLIED CHEMISTRY JIANGXI ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410886409.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2025-03-04
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

The energy storage density of existing phase change energy storage materials is low, and after multiple phase change cycles, due to the low thermal conductivity and uneven components of the material, the energy storage efficiency and cycle stability are reduced.

Method used

By using the preparation method of organic and inorganic hybrid phase change energy storage materials, the thermal conductivity and loading performance of the load carrier are optimized by loading the modified polyethylene glycol onto the active carrier and forming a double-layer coated structure of paraffin and modified chitosan on the outside of the load carrier.

Benefits of technology

The anti-leakage performance, energy storage density, thermal conductivity and thermal cycle stability of phase change energy storage materials are improved, and the thermal stability and mechanical strength of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004926172030000171
    Figure BDA0004926172030000171
  • Figure BDA0004926172030000181
    Figure BDA0004926172030000181
  • Figure BDA0004926172030000182
    Figure BDA0004926172030000182
Patent Text Reader

Abstract

The invention discloses a preparation method of an organic-inorganic hybrid phase change energy storage material, belonging to the technical field of energy storage material processing. The invention comprises the following steps: adding polyethylene glycol, tridecanedioic acid, toluene and a catalyst into a reactor and stirring, raising the temperature of the reactor to 80-90°C, and keeping the temperature for reaction for 6-8h; during the reaction, removing by-products through a water separator, and post-processing to obtain modified polyethylene glycol. The invention improves the energy storage performance of polyethylene glycol and the outer shell structure of the phase change energy storage material by optimizing the thermal conductivity and load performance of the load carrier, thereby effectively improving the anti-leakage performance and energy storage density of the phase change energy storage material, and also improving the thermal conductivity and thermal cycle stability of the phase change energy storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage material processing, and in particular to a method for preparing an organic-inorganic hybrid phase change energy storage material. Background Art

[0002] Phase change material is a material that can absorb or release a large amount of heat within a specific temperature range. The phase change process of phase change material can be used to absorb and release heat in an environment with a large temperature difference between day and night, thereby reducing the dependence of buildings on traditional heating and cooling equipment and achieving efficient use of energy. With the global energy crisis and increasing awareness of environmental protection, building energy conservation has become an important development direction of the construction industry. The energy consumption of buildings is mainly concentrated in heating, ventilation, air conditioning, etc., among which the energy consumption of air conditioning systems accounts for a large proportion. In order to reduce the energy consumption of buildings during cooling and heating, phase change materials are introduced into the construction field as a new type of energy storage material. Phase change energy storage technology can not only reduce energy consumption during the operation of buildings, but also improve indoor comfort and reduce carbon emissions of buildings. It has broad application prospects.

[0003] The preparation methods of phase change energy storage materials in the prior art mainly include sol-gel method, in-situ polymerization method, interface modification method, etc. Among them, the sol-gel method can control the microstructure and performance of the material by adjusting the composition and gelation conditions of the sol, the in-situ polymerization method can realize the synchronous synthesis of inorganic and organic components to form an ordered structure, and the interface modification method can regulate the structure and performance of the material by changing the interface characteristics;

[0004] However, organic phase change materials such as alkanes, fatty acids, and polyols have relatively simple molecular structures and can store limited energy per unit volume. Organic phase change materials are loaded on inorganic phase change materials by simple adsorption, and organic phase change materials are prone to leak from energy storage materials. Although inorganic phase change materials have higher energy storage density, most of them have obvious phase separation and higher supercooling. These problems make it difficult for the actual energy storage density of inorganic phase change materials to be fully utilized, resulting in a lower energy storage density of phase change energy storage materials.

[0005] Moreover, after multiple phase change cycles, phase change materials may experience phase separation due to the low thermal conductivity of the material itself, the uneven distribution of components within the material, or the volume change during the phase transition. Phase separation will reduce the energy storage efficiency and cycle stability of the material, resulting in the need for further improvement in energy storage performance and cycle stability.

[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an organic-inorganic hybrid phase change energy storage material to solve the technical defects proposed by the background technology.

[0008] The purpose of the present invention can be achieved by the following technical solution: A method for preparing an organic-inorganic hybrid phase change energy storage material comprises the following steps:

[0009] S1, adding polyethylene glycol, tridecanedioic acid, toluene and a catalyst into a reaction kettle and stirring, raising the temperature of the reaction kettle to 80-90°C, and keeping the temperature for reaction for 6-8h. During the reaction, by-products are separated by a water separator, and modified polyethylene glycol is obtained by post-treatment;

[0010] The synthetic reaction principle of modified polyethylene glycol is:

[0011] Under the action of the catalyst, the hydroxyl group on the polyethylene glycol and the carboxyl group on the tridecanedioic acid undergo esterification reaction to form an ester bond. During the reaction, water is continuously removed as a by-product through a water separator, thereby promoting the reaction in the direction of ester formation, introducing a large number of ester bonds into the modified polyethylene glycol, and improving the cross-linking degree of the modified polyethylene glycol.

[0012] S2, adding modified polyethylene glycol and diluent to a reactor and stirring, raising the temperature of the reactor to 80-90°C, adding active carrier to the reactor, stirring for 30-50min, adding dopamine hydrochloride to the reactor, evacuating the pressure of the reactor to -0.1MPa, distilling off the solvent under reduced pressure, keeping warm, the pressure of the reactor continuously increased to 0.2MPa, and then evacuating to -0.1MPa, repeating the operation 3-5 times, under vacuum environment, lowering the temperature of the reactor to 10-15°C, discharging, and obtaining a loaded carrier;

[0013] The preparation mechanism of the load carrier is:

[0014] Dopamine hydrochloride undergoes a self-assembly reaction in a dilute liquid environment, promoting the cross-linking of modified polyethylene glycol and the active carrier to form a network cross-linking structure. The modified polyethylene glycol is then treated with high pressure and negative pressure under a high temperature environment to allow the modified polyethylene glycol to enter the active carrier, and its solidification is promoted by low temperature to prepare a loaded carrier.

[0015] S3. Add the emulsion and the load carrier into the reactor and stir. Slowly add the paraffin solution and the modified chitosan dispersion into the reactor in turn at room temperature. Raise the temperature of the reactor to 75-85°C, keep warm and stir for 20-30 minutes, add o-phthalaldehyde into the reactor, keep warm and react for 4-6 hours, and obtain the phase change energy storage material by post-processing.

[0016] The synthetic reaction principle of phase change energy storage materials is:

[0017] The method comprises the following steps: uniformly dispersing paraffin wax, modified chitosan and a load carrier in an emulsion, forming a coating on the outside of the load carrier in the emulsion, wherein the paraffin wax can provide an initial coating for the load carrier, and the aldehyde group of o-phthalaldehyde can react with the hydroxyl group on the modified chitosan molecule to form an ester bond, thereby further enhancing the stability and mechanical strength of the coating layer, thereby forming a double-layer coating structure of paraffin wax and modified chitosan on the outside of the load carrier, and preparing a phase change energy storage material.

[0018] Further, in step S1, the amount ratio of the polyethylene glycol, tridecanedioic acid, toluene and catalyst is 10g:1-2g:150mL:0.1-0.5g, the polyethylene glycol is polyethylene glycol 6000, and the catalyst is titanium n-butoxide. The post-treatment comprises: after the reaction is completed, the temperature of the reactor is kept at 80-90°C, and the solvent is evaporated under reduced pressure to obtain modified polyethylene glycol; in step S2, the diluent is a 0.5 mol / L tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8.5, and the modified polyethylene The dosage ratio of diol, diluent, active carrier and dopamine hydrochloride is 5g:40mL:13g:2g; in step S3, the dosage ratio of the emulsion, load carrier, paraffin solution, modified chitosan dispersion and o-phthalaldehyde is 20mL:5g:10g:10mL:0.5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and vacuum dried to constant weight to obtain a phase change energy storage material.

[0019] Further, in step S2, the active carrier is processed by the following steps:

[0020] A1. Add pine sawdust and pretreatment solution into a reactor and stir. Raise the temperature of the reactor to 65-75°C and keep warm for 2-3 hours. Post-treat to obtain pretreated sawdust.

[0021] A2, adding the pretreated sawdust and copper acetate solution into the reactor, raising the temperature of the reactor to 55-65°C, ultrasonically dispersing for 2-3h, and post-treating to obtain loaded sawdust;

[0022] A3. Add the loaded wood chips into a tubular furnace and perform programmed calcination to prepare an active carrier.

[0023] Further, in step A1, the pretreatment solution is composed of potassium hydroxide, N-methylpyrrolidone and purified water in a dosage ratio of 4g:10mL:15mL, the dosage ratio of the pine sawdust and the pretreatment solution is 1g:10mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70-80°C and dried to constant weight to obtain pretreated sawdust; in step A2, the copper acetate solution is composed of polyethyleneimine, copper acetate, and anhydrous ethanol in a dosage ratio of 2g:1g:15mL. The pretreated sawdust and the copper acetate solution are used in a ratio of 3g:5mL, and the post-treatment includes: after the reaction is completed, heat preservation, and evaporation under reduced pressure to remove the solvent to obtain loaded sawdust; in step A3, the programmed calcination includes: in an oxygen atmosphere, the temperature of the tube furnace is increased to 100-120°C at a heating rate of 3°C / min, and heat preservation is performed for 1-2h, nitrogen is introduced into the tube furnace to replace the oxygen in the tube furnace, and in a nitrogen environment, the tube furnace is heated to 600-800°C at a heating rate of 5°C / min, and heat preservation is performed for 3-5h, and the tube furnace is naturally cooled to room temperature to obtain an active carrier.

[0024] Furthermore, in step S3, the preparation method of the emulsion is: adding petroleum ether, purified water, and a dispersant into a reactor and stirring to obtain an emulsion, wherein the amount ratio of the petroleum ether, purified water, and dispersant is 5mL:3mL:0.1g, the dispersant is composed of sodium stearate and sodium dodecyl sulfate in a weight ratio of 2:1, and the boiling range of the petroleum ether is 90-120°C.

[0025] Furthermore, in step S3, the paraffin solution is prepared by adding paraffin and petroleum ether in a dosage ratio of 1 g: 5-7 mL into a reactor, stirring until the system is dissolved, to obtain a paraffin solution.

[0026] Further, in step S3, the modified chitosan dispersion is obtained by processing the following steps:

[0027] B1. Add chitosan and N,N-dimethylformamide into a reactor, swell for 8-10 hours at room temperature, fill the reactor with nitrogen to replace the air therein, add modified carbon nanotubes into the reactor under stirring, increase the temperature of the reactor to 130-140° C., keep warm and stir for 60-80 hours, and post-treat to obtain modified chitosan;

[0028] The synthetic reaction principle of modified chitosan is:

[0029] Since the modified carbon nanotubes have acyl chloride groups on their surfaces, these groups have high reactivity with amino groups or hydroxyl groups in chitosan molecules, so the modified carbon nanotubes are loaded on chitosan to prepare modified chitosan.

[0030] B2. Add modified chitosan, sodium dodecyl sulfate and purified water into a reactor and stir evenly. Add glacial acetic acid into the reactor and stir at room temperature for 30-50 minutes to obtain a modified chitosan dispersion.

[0031] Furthermore, in step B1, the amount ratio of the chitosan, N,N-dimethylformamide and modified carbon nanotubes is 10g:100mL:3-5g, the deacetylation degree of the chitosan is 80-90%, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is kept at 130-140°C, and the solvent is evaporated under reduced pressure to obtain modified chitosan; in step B2, the amount ratio of the modified chitosan, sodium dodecyl sulfate, purified water and glacial acetic acid is 2g:0.1g:15mL:0.5g.

[0032] Furthermore, in step B1, the modified carbon nanotubes are obtained by processing the following steps:

[0033] C1. Add multi-walled carbon nanotubes and activation solution into a reaction kettle and stir, raise the temperature of the reaction kettle to reflux the system, keep the temperature for 2-3 hours, and post-treat to obtain activated carbon nanotubes;

[0034] C2. Add activated carbon nanotubes and thionyl chloride into a reactor and stir. Raise the temperature of the reactor to 60-70° C. and keep the temperature for 18-20 hours. Post-treat to obtain modified carbon nanotubes.

[0035] The synthetic reaction principle of modified carbon nanotubes is:

[0036] In the high-temperature activation liquid environment, the activation liquid can oxidize the carbon atoms on the surface of the carbon nanotubes to form oxygen-containing functional groups, thereby enhancing the chemical activity of the carbon nanotubes; thionyl chloride, as an acyl chlorination reagent, can react with the oxygen-containing functional groups on the surface of the activated carbon nanotubes to generate acyl chloride groups, thereby preparing high-efficiency carbon nanotubes.

[0037] Furthermore, in step C1, the amount ratio of the multi-walled carbon nanotubes to the activation solution is 1g:5-6mL, the activation solution is composed of 80-90wt% sulfuric acid and 70-80wt% nitric acid in a volume ratio of 2:1, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with purified water 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain activated carbon nanotubes; in step C2, the amount ratio of the activated carbon nanotubes to thionyl chloride is 1g:4-6mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with tetrahydrofuran 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and dried to constant weight to obtain modified carbon nanotubes.

[0038] The present invention has the following beneficial effects:

[0039] 1. The organic-inorganic hybrid phase change energy storage material of the present invention is prepared by selecting pine sawdust as raw material, pre-treating and loading it, and then loading and program calcining it to prepare a porous active carrier loaded with copper oxide. The phase change energy storage material is prepared by loading modified polyethylene glycol onto the active carrier and forming a two-component coating layer of paraffin and modified chitosan on the outside of the loaded carrier. The thermal conductivity and loading performance of the loaded carrier, the energy storage performance of polyethylene glycol and the outer shell structure of the phase change energy storage material are optimized, thereby improving the anti-leakage performance, energy storage density, thermal conductivity and thermal cycle stability of the phase change energy storage material.

[0040] 2. The organic-inorganic hybrid phase change energy storage material of the present invention is prepared by pre-treating pine sawdust and then loading it to obtain a porous active carrier with loaded copper oxide and amino-containing carbonized slag, and by increasing the loading capacity of the active carrier and the thermal conductivity of the active carrier itself under high temperature. When loading modified polyethylene glycol, dopamine hydrochloride is used as a cross-linking agent, and a layer of polydopamine is coated on the active carrier to promote the cross-linking of the modified polyethylene glycol and the active carrier. After high-pressure and low-pressure cycle treatment, the modified polyethylene glycol is loaded on the active carrier to prepare a loaded carrier. The introduction of polydopamine can significantly improve the adhesion and wettability of the material. Dopamine has super strong adhesion and good biocompatibility. Therefore, when it forms a coating layer on the active carrier, it can effectively enhance the binding force between the modified polyvinyl alcohol and the active carrier, thereby reducing or preventing the leakage of the modified ethylene glycol and improving the overall anti-leakage performance of the phase change material; polyethylene glycol is modified by tridecanedioic acid, ester bonds are introduced into the polyethylene glycol molecules, and the network structure of the modified polyethylene glycol and the cross-linking points between the molecular chains are increased, thereby improving its thermal stability and energy storage performance. In addition, the increase in the degree of cross-linking can enable the modified polyethylene glycol to better maintain its shape and structure when heated, reduce thermal deformation and flow, and thus improve its energy storage density and efficiency.

[0041] 3. The organic-inorganic hybrid phase change energy storage material of the present invention is prepared by coating the outside of the load carrier with a shell layer coated with paraffin and modified chitosan. The chitosan is modified so that multi-walled carbon nanotubes are loaded on the chitosan. Chitosan, as a natural organic high molecular linear polysaccharide, has good film-forming properties and mechanical properties. By forming a microcapsule shell structure on the outside of the load carrier, chitosan can further exert its mechanical properties and improve the strength and toughness of the coating layer. Multi-walled carbon nanotubes are used as high thermal conductivity reinforcement materials. Chitosan can be modified to improve the thermal conductivity of the coating shell, which helps to improve the overall thermal properties of the microcapsule phase change material and improve the heat transfer efficiency. Chitosan can also stabilize the paraffin particle dispersion to make it present a more uniform dispersion state and reduce the particle size of the paraffin. The microcapsule structure formed by chitosan as a coating layer can protect the paraffin, improve the thermal stability and thermal cycle stability of the paraffin, and then ensure the integrity of the shell layer, prevent the phase change energy storage material from directly contacting the external environment during the phase change process, thereby slowing down its performance decay. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing modified chitosan for organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0045] S1. Preparation of activated carbon nanotubes

[0046] 80 wt % sulfuric acid and 70 wt % nitric acid were mixed uniformly in a volume ratio of 2:1 to obtain an activation solution for later use;

[0047] Weigh: 5 g of multi-walled carbon nanotubes and 25 mL of activation solution are added to the reactor and stirred. The temperature of the reactor is raised to reflux and the system is kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed three times with purified water and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and dried to constant weight to obtain activated carbon nanotubes.

[0048] S2. Preparation of modified carbon nanotubes

[0049] Weigh: 5 g of activated carbon nanotubes and 20 mL of thionyl chloride are added to a reactor and stirred. The temperature of the reactor is raised to 60°C and kept warm for 18 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with tetrahydrofuran three times and then dried. The filter cake is transferred to a drying oven at a temperature of 50°C and dried to constant weight to obtain modified carbon nanotubes.

[0050] S3. Preparation of modified chitosan

[0051] Weigh: 10 g of chitosan and 100 mL of N,N-dimethylformamide are added to a reactor, swelled at room temperature for 8 hours, nitrogen is filled into the reactor to replace the air therein, 3 g of modified carbon nanotubes are added to the reactor under stirring, the temperature of the reactor is increased to 130°C, and the mixture is kept warm and stirred for 60 hours. After the reaction is completed, the temperature of the reactor is kept at 130°C, and the solvent is evaporated under reduced pressure to obtain modified chitosan, wherein the degree of deacetylation of the chitosan is 80%.

[0052] Example 2

[0053] This embodiment provides a method for preparing modified chitosan for organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0054] S1. Preparation of activated carbon nanotubes

[0055] 85 wt % sulfuric acid and 75 wt % nitric acid were mixed uniformly in a volume ratio of 2:1 to obtain an activation solution for later use;

[0056] Weigh: 5 g of multi-walled carbon nanotubes and 27 mL of activation solution, add them into the reactor and stir, raise the temperature of the reactor to reflux, and keep warm for 2.5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water three times and then dry it, transfer the filter cake to a drying oven at 75°C, and dry it to constant weight to obtain activated carbon nanotubes.

[0057] S2. Preparation of modified carbon nanotubes

[0058] Weigh: 5 g of activated carbon nanotubes and 40 mL of thionyl chloride are added to a reactor and stirred. The temperature of the reactor is raised to 65°C and kept warm for 19 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with tetrahydrofuran three times and then dried. The filter cake is transferred to a drying oven at a temperature of 55°C and dried to constant weight to obtain modified carbon nanotubes.

[0059] S3. Preparation of modified chitosan

[0060] Weigh: 10 g of chitosan and 100 mL of N,N-dimethylformamide are added to a reactor, swelled at room temperature for 9 hours, nitrogen is filled into the reactor to replace the air therein, 4 g of modified carbon nanotubes are added to the reactor under stirring, the temperature of the reactor is increased to 135°C, and the mixture is kept warm and stirred for 70 hours. After the reaction is completed, the temperature of the reactor is kept at 135°C, and the solvent is evaporated under reduced pressure to obtain modified chitosan, wherein the degree of deacetylation of the chitosan is 85%.

[0061] Example 3

[0062] This embodiment provides a method for preparing modified chitosan for organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0063] S1. Preparation of activated carbon nanotubes

[0064] 90 wt % sulfuric acid and 80 wt % nitric acid are mixed uniformly in a volume ratio of 2:1 to obtain an activation solution for later use;

[0065] Weigh: 5 g of multi-walled carbon nanotubes and 30 mL of activation solution are added to the reactor and stirred. The temperature of the reactor is raised to reflux and the system is kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed three times with purified water and then dried. The filter cake is transferred to a drying oven at 80°C and dried to constant weight to obtain activated carbon nanotubes.

[0066] S2. Preparation of modified carbon nanotubes

[0067] Weigh: 5 g of activated carbon nanotubes and 60 mL of thionyl chloride are added to a reactor and stirred. The temperature of the reactor is raised to 70°C and kept warm for 20 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with tetrahydrofuran three times and then dried. The filter cake is transferred to a drying oven at a temperature of 60°C and dried to constant weight to obtain modified carbon nanotubes.

[0068] S3. Preparation of modified chitosan

[0069] Weigh: 10 g of chitosan and 100 mL of N,N-dimethylformamide are added to a reactor, swelled at room temperature for 10 hours, nitrogen is filled into the reactor to replace the air therein, and 5 g of modified carbon nanotubes are added to the reactor under stirring. The temperature of the reactor is increased to 140°C, and the mixture is kept warm and stirred for 80 hours. After the reaction is completed, the temperature of the reactor is kept at 140°C, and the solvent is evaporated under reduced pressure to obtain modified chitosan, wherein the degree of deacetylation of the chitosan is 90%.

[0070] Example 4

[0071] This embodiment provides a method for preparing an organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0072] Step 1: Preparation of modified polyethylene glycol

[0073] Weigh: 50 g of polyethylene glycol 6000, 5 g of tridecanedioic acid, 7500 mL of toluene and 0.5 g of titanium n-butoxide, add them into a reactor and stir, raise the temperature of the reactor to 80°C, and keep the reaction for 6 hours. During the reaction, the by-products are separated by a water separator. After the reaction is completed, the temperature of the reactor is kept at 80°C, and the solvent is evaporated under reduced pressure to obtain modified polyethylene glycol.

[0074] Step 2: Preparation of active carrier

[0075] Mix potassium hydroxide, N-methylpyrrolidone and purified water in a ratio of 4 g:10 mL:15 mL to obtain a pretreatment solution for later use;

[0076] Weigh: 100 g of pine sawdust and 1 L of pretreatment solution are added to the reactor and stirred. The temperature of the reactor is raised to 65°C and kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and dried to constant weight to obtain pretreated sawdust;

[0077] Mix polyethyleneimine, copper acetate and anhydrous ethanol in a ratio of 2g:1g:15mL to obtain a copper acetate solution for later use;

[0078] Weigh: 60 g of pretreated sawdust and 100 mL of copper acetate solution are added into a reactor, the temperature of the reactor is raised to 55° C., ultrasonic dispersion is performed for 2 h, the temperature is kept, and the solvent is evaporated under reduced pressure to obtain loaded sawdust;

[0079] The loaded wood chips were added into a tubular furnace. In an oxygen atmosphere, the temperature of the tubular furnace was increased to 100°C at a heating rate of 3°C / min and kept warm for 1 hour. Nitrogen was introduced into the tubular furnace to replace the oxygen in the tubular furnace. In a nitrogen environment, the temperature of the tubular furnace was increased to 600°C at a heating rate of 5°C / min and kept warm for 3 hours. The tubular furnace was naturally cooled to room temperature to obtain an active carrier.

[0080] Step 3: Prepare the load carrier

[0081] Weigh: 50 g of modified polyethylene glycol and 400 mL of 0.5 mol / L tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8.5, add them to a reactor and stir, raise the temperature of the reactor to 80° C., add 130 g of active carrier to the reactor, stir for 30 min, add 20 g of dopamine hydrochloride to the reactor, evacuate the reactor until the pressure is -0.1 MPa, evaporate the solvent under reduced pressure, keep warm, increase the pressure of the reactor to 0.2 MPa, then evacuate to -0.1 MPa, repeat the operation 3 times, lower the temperature of the reactor to 10° C. under vacuum, discharge the material, and obtain a loaded carrier.

[0082] Step 4: Preparation of phase change energy storage materials

[0083] Prepare emulsion: add petroleum ether with a boiling range of 90-120°C, purified water, and dispersant in a ratio of 5mL:3mL:0.1g into a reaction kettle and stir evenly to obtain an emulsion for standby use, wherein the dispersant is composed of sodium stearate and sodium dodecyl sulfate in a weight ratio of 2:1;

[0084] Add paraffin wax and petroleum ether in a ratio of 1 g:5 mL into the reactor and stir until the system is dissolved to obtain a paraffin solution for later use;

[0085] Weigh: 6 g of the modified chitosan prepared in Example 1, 0.3 g of sodium dodecyl sulfate, and 45 mL of purified water, add them into a reactor and stir evenly, add 1.5 g of glacial acetic acid into the reactor, stir at room temperature for 30 min, and obtain a modified chitosan dispersion for later use;

[0086] Weigh: 400 mL of emulsion and 100 g of load carrier are added to the reactor and stirred. 200 g of paraffin solution and 200 g of modified chitosan dispersion are slowly added to the reactor in turn at room temperature. The temperature of the reactor is raised to 75°C, and the mixture is kept warm and stirred for 20 minutes. 10 g of o-phthalaldehyde is added to the reactor, and the mixture is kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed 3 times with purified water and then dried. The filter cake is transferred to a drying oven at 50°C and vacuum dried to constant weight to obtain a phase change energy storage material.

[0087] Example 5

[0088] This embodiment provides a method for preparing an organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0089] Step 1: Preparation of modified polyethylene glycol

[0090] Weigh: 50 g of polyethylene glycol 6000, 7 g of tridecanedioic acid, 7500 mL of toluene and 1.5 g of titanium n-butoxide, add into a reactor and stir, raise the temperature of the reactor to 85°C, and keep the reaction for 7 hours. During the reaction, the by-products are separated by a water separator. After the reaction is completed, the temperature of the reactor is kept at 85°C, and the solvent is evaporated under reduced pressure to obtain modified polyethylene glycol.

[0091] Step 2: Preparation of active carrier

[0092] Mix potassium hydroxide, N-methylpyrrolidone and purified water in a ratio of 4 g:10 mL:15 mL to obtain a pretreatment solution for later use;

[0093] Weigh: 100 g of pine sawdust and 1 L of pretreatment solution, add them into the reactor and stir, raise the temperature of the reactor to 70°C, and keep it warm for 2.5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain it. Transfer the filter cake to a drying oven at a temperature of 75°C and dry it to constant weight to obtain pretreated sawdust;

[0094] Mix polyethyleneimine, copper acetate and anhydrous ethanol in a ratio of 2g:1g:15mL to obtain a copper acetate solution for later use;

[0095] Weigh: 60 g of pretreated sawdust and 100 mL of copper acetate solution are added into a reactor, the temperature of the reactor is raised to 60° C., ultrasonic dispersion is performed for 2.5 h, the temperature is maintained, and the solvent is evaporated under reduced pressure to obtain loaded sawdust;

[0096] The loaded wood chips were added into a tubular furnace. In an oxygen atmosphere, the temperature of the tubular furnace was increased to 110°C at a heating rate of 3°C / min and kept warm for 1.5 hours. Nitrogen was introduced into the tubular furnace to replace the oxygen in the tubular furnace. In a nitrogen environment, the temperature of the tubular furnace was increased to 700°C at a heating rate of 5°C / min and kept warm for 4 hours. The tubular furnace was naturally cooled to room temperature to obtain an active carrier.

[0097] Step 3: Prepare the load carrier

[0098] Weigh: 50 g of modified polyethylene glycol and 400 mL of 0.5 mol / L tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8.5, add them into a reactor and stir, raise the temperature of the reactor to 85° C., add 130 g of active carrier into the reactor, stir for 40 min, add 20 g of dopamine hydrochloride into the reactor, evacuate the reactor until the pressure is -0.1 MPa, remove the solvent under reduced pressure, keep warm, increase the pressure of the reactor to 0.2 MPa, then evacuate to -0.1 MPa, repeat the operation 4 times, lower the temperature of the reactor to 13° C. under vacuum, discharge the material, and obtain a loaded carrier.

[0099] Step 4: Preparation of phase change energy storage materials

[0100] Prepare emulsion: add petroleum ether with a boiling range of 90-120°C, purified water, and dispersant in a ratio of 5mL:3mL:0.1g into a reaction kettle and stir evenly to obtain an emulsion for standby use, wherein the dispersant is composed of sodium stearate and sodium dodecyl sulfate in a weight ratio of 2:1;

[0101] Add paraffin wax and petroleum ether in a ratio of 1 g:6 mL into the reactor and stir until the system is dissolved to obtain a paraffin solution for later use;

[0102] Weigh: 6 g of the modified chitosan prepared in Example 2, 0.3 g of sodium dodecyl sulfate, and 45 mL of purified water, add them into a reactor and stir evenly, add 1.5 g of glacial acetic acid into the reactor, stir at room temperature for 40 min, and obtain a modified chitosan dispersion for later use;

[0103] Weigh: 400 mL of emulsion and 100 g of load carrier are added to the reactor and stirred. 200 g of paraffin solution and 200 g of modified chitosan dispersion are slowly added to the reactor in turn at room temperature. The temperature of the reactor is raised to 80°C, and the mixture is kept warm and stirred for 25 minutes. 10 g of o-phthalaldehyde is added to the reactor, and the mixture is kept warm for 5 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed three times with purified water and then dried. The filter cake is transferred to a drying oven at 55°C and vacuum dried to constant weight to obtain a phase change energy storage material.

[0104] Example 6

[0105] This embodiment provides a method for preparing an organic-inorganic hybrid phase change energy storage material, comprising the following steps:

[0106] Step 1: Preparation of modified polyethylene glycol

[0107] Weigh: 50 g of polyethylene glycol 6000, 10 g of tridecanedioic acid, 7500 mL of toluene and 2.5 g of titanium n-butoxide, add them into a reactor and stir, raise the temperature of the reactor to 90°C, and keep the reaction for 8 hours. During the reaction, the by-products are separated by a water separator. After the reaction is completed, the temperature of the reactor is kept at 90°C, and the solvent is evaporated under reduced pressure to obtain modified polyethylene glycol.

[0108] Step 2: Preparation of active carrier

[0109] Mix potassium hydroxide, N-methylpyrrolidone and purified water in a ratio of 4 g:10 mL:15 mL to obtain a pretreatment solution for later use;

[0110] Weigh: 100 g of pine sawdust and 1 L of pretreatment solution, add them into the reactor and stir, raise the temperature of the reactor to 75°C, and keep it warm for 3 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain it. Transfer the filter cake to a drying oven at 80°C and dry it to constant weight to obtain pretreated sawdust;

[0111] Mix polyethyleneimine, copper acetate and anhydrous ethanol in a ratio of 2g:1g:15mL to obtain a copper acetate solution for later use;

[0112] Weigh: 60 g of pretreated sawdust and 100 mL of copper acetate solution are added into a reactor, the temperature of the reactor is raised to 65°C, ultrasonic dispersion is performed for 3 h, the temperature is kept, and the solvent is evaporated under reduced pressure to obtain loaded sawdust;

[0113] The loaded wood chips were added into a tubular furnace. In an oxygen atmosphere, the temperature of the tubular furnace was increased to 120°C at a heating rate of 3°C / min and kept warm for 2 hours. Nitrogen was introduced into the tubular furnace to replace the oxygen in the tubular furnace. In a nitrogen environment, the temperature of the tubular furnace was increased to 800°C at a heating rate of 5°C / min and kept warm for 5 hours. The tubular furnace was naturally cooled to room temperature to obtain an active carrier.

[0114] Step 3: Prepare the load carrier

[0115] Weigh: 50 g of modified polyethylene glycol and 400 mL of 0.5 mol / L tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8.5, add them to a reactor and stir, raise the temperature of the reactor to 90° C., add 130 g of an active carrier to the reactor, stir for 50 min, add 20 g of dopamine hydrochloride to the reactor, evacuate the reactor until the pressure is -0.1 MPa, evaporate the solvent under reduced pressure, keep warm, and continuously raise the pressure of the reactor to 0.2 MPa, then evacuate to -0.1 MPa, repeat the operation 5 times, lower the temperature of the reactor to 15° C. under vacuum, discharge the material, and obtain a loaded carrier.

[0116] Step 4: Preparation of phase change energy storage materials

[0117] Prepare emulsion: add petroleum ether with a boiling range of 90-120°C, purified water, and dispersant in a ratio of 5mL:3mL:0.1g into a reaction kettle and stir evenly to obtain an emulsion for standby use, wherein the dispersant is composed of sodium stearate and sodium dodecyl sulfate in a weight ratio of 2:1;

[0118] Add paraffin wax and petroleum ether in a ratio of 1 g:7 mL into the reactor and stir until the system is dissolved to obtain a paraffin solution for later use;

[0119] Weigh: 6 g of the modified chitosan prepared in Example 3, 0.3 g of sodium dodecyl sulfate, and 45 mL of purified water, add them into a reactor and stir evenly, add 1.5 g of glacial acetic acid into the reactor, stir at room temperature for 50 min, and obtain a modified chitosan dispersion for later use;

[0120] Weigh: 400 mL of emulsion and 100 g of load carrier are added to the reactor and stirred. 200 g of paraffin solution and 200 g of modified chitosan dispersion are slowly added to the reactor in turn at room temperature. The temperature of the reactor is raised to 85°C, and the mixture is kept warm and stirred for 30 minutes. 10 g of o-phthalaldehyde is added to the reactor, and the mixture is kept warm for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed 3 times with purified water and then dried. The filter cake is transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain a phase change energy storage material.

[0121] Comparative Example 1

[0122] The difference between this comparative example and Example 6 is that step 1 is eliminated, and the modified polyethylene glycol in step 3 is replaced by polyethylene glycol 6000 in step 1.

[0123] Comparative Example 2

[0124] The difference between this comparative example and Example 6 is that in step 2, polyethyleneimine is not added to the copper acetate solution.

[0125] Comparative Example 3

[0126] The difference between this comparative example and Example 6 is that in step 3, dopamine hydrochloride is not added.

[0127] Comparative Example 4

[0128] The difference between this comparative example and Example 6 is that the modified chitosan prepared in Example 3 used in step 4 is replaced by an equal amount of chitosan in Example 3.

[0129] Performance Testing:

[0130] The energy storage density, thermal conductivity, thermal stability, thermal cycle stability and leakage performance of the phase change energy storage materials prepared in Examples 4-6 and Comparative Examples 1-4 were tested, wherein the energy storage density was measured by referring to the standard JC / T2111-2012 "Test Method for Phase Change Temperature Regulation Performance of Building Materials" to determine the phase change latent heat of the sample, and the thermal conductivity was measured by referring to the standard GB / T 10297-2015 "Hot Wire Method for Determination of Thermal Conductivity of Non-metallic Solid Materials" to determine the thermal conductivity of the sample; the thermal stability was measured by referring to the standard JG / T 534-2018 "Test Method for Thermal Reliability of Phase Change Materials for Buildings" to determine the melting temperature and solidification temperature of the sample; the thermal cycle stability was measured by measuring the phase change latent heat, melting temperature, solidification temperature and thermal conductivity of the sample after the sample was accelerated cycled 100 times, and the leakage performance was measured by measuring the mass change rate of the sample after the sample was accelerated cycled 100 times. The specific measurement results are shown in Tables 1 and 2.

[0131] Table 1- Performance test data of samples before accelerated cycling

[0132]

[0133]

[0134] Table 2- Performance test data of samples after 100 accelerated cycles

[0135]

[0136] Performance Testing:

[0137] Comparing and analyzing the data in Table 1 and Table 2, the phase change energy storage material prepared by the present invention has a phase change latent heat of 233.6 J / g, a melting temperature of 57.73°C, a solidification temperature of 56.82°C, and a thermal conductivity of 0.613 W / (m·k) before the accelerated cycle. After 100 accelerated cycles, the phase change latent heat of the sample reaches 228.8 J / g, the melting temperature reaches 56.91°C, the solidification temperature reaches 56.05°C, and the thermal conductivity reaches 0.581W / (m·k), the mass change rate is reduced to 0.72%, and various performance test data are better than those of the comparative example, indicating that the present invention optimizes the thermal conductivity and loading performance of the loading carrier by pretreating and loading the pine sawdust, improves the energy storage performance of polyethylene glycol and the outer shell structure of the phase change energy storage material, effectively improves the anti-leakage performance and phase change latent heat of the phase change energy storage material, and also improves the thermal conductivity and thermal cycle stability of the phase change energy storage material.

[0138] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0139] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0140] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing an organic-inorganic hybrid phase change energy storage material, characterized in that: The following steps are involved: S1, adding polyethylene glycol, tridecanedioic acid, toluene and a catalyst into a reaction kettle and stirring, raising the temperature of the reaction kettle to 80-90°C, and keeping the temperature for reaction for 6-8h. During the reaction, by-products are separated by a water separator, and modified polyethylene glycol is obtained by post-treatment; S2, adding modified polyethylene glycol and diluent to a reactor and stirring, raising the temperature of the reactor to 80-90°C, adding active carrier to the reactor, stirring for 30-50min, adding dopamine hydrochloride to the reactor, evacuating the pressure of the reactor to -0.1MPa, distilling off the solvent under reduced pressure, keeping warm, the pressure of the reactor continuously increased to 0.2MPa, and then evacuating to -0.1MPa, repeating the operation 3-5 times, under vacuum environment, lowering the temperature of the reactor to 10-15°C, discharging, and obtaining a loaded carrier; S3, adding the emulsion and the load carrier into the reactor and stirring, slowly adding the paraffin solution and the modified chitosan dispersion into the reactor in sequence at room temperature, raising the temperature of the reactor to 75-85°C, keeping warm and stirring for 20-30 minutes, adding o-phthalaldehyde into the reactor, keeping warm and reacting for 4-6 hours, and post-processing to obtain the phase change energy storage material; The active carrier is processed by the following steps: A1. Add pine sawdust and pretreatment solution into a reactor and stir. Raise the temperature of the reactor to 65-75°C, keep warm for 2-3h, and post-treat to obtain pretreated sawdust. The pretreatment solution is composed of potassium hydroxide, N-methylpyrrolidone and purified water in a ratio of 4g:10mL:15mL, and the ratio of pine sawdust to pretreatment solution is 1g:10mL. A2, adding pretreated sawdust and copper acetate solution into a reactor, raising the temperature of the reactor to 55-65°C, ultrasonically dispersing for 2-3h, and post-treating to obtain loaded sawdust, wherein the copper acetate solution is composed of polyethyleneimine, copper acetate, and anhydrous ethanol in a dosage ratio of 2g:1g:15mL, and the dosage ratio of the pretreated sawdust and copper acetate solution is 3g:5mL; A3, adding the loaded sawdust into a tubular furnace, and performing a programmed calcination to prepare an active carrier, wherein the programmed calcination comprises: in an oxygen atmosphere, the temperature of the tubular furnace is increased to 100-120°C at a heating rate of 3°C / min, and the temperature is kept at this temperature for 1-2 hours, nitrogen is introduced into the tubular furnace to replace the oxygen in the tubular furnace, and in a nitrogen environment, the temperature of the tubular furnace is increased to 600-800°C at a heating rate of 5°C / min, and the temperature is kept at this temperature for 3-5 hours, and the tubular furnace is naturally cooled to room temperature to obtain an active carrier; The modified chitosan dispersion is obtained by processing the following steps: B1. Add chitosan and N,N-dimethylformamide into a reactor, swell for 8-10 hours at room temperature, fill the reactor with nitrogen to replace the air therein, add modified carbon nanotubes into the reactor under stirring, increase the temperature of the reactor to 130-140° C., keep warm and stir for 60-80 hours, and post-treat to obtain modified chitosan; B2, adding modified chitosan, sodium lauryl sulfate and purified water into a reactor and stirring evenly, adding glacial acetic acid into the reactor, stirring at room temperature for 30-50 minutes, and obtaining a modified chitosan dispersion; The modified carbon nanotubes are obtained by processing the following steps: C1. Add multi-walled carbon nanotubes and activation solution into a reactor and stir. Raise the temperature of the reactor to reflux the system and keep the temperature for 2-3 hours. Post-treat to obtain activated carbon nanotubes. C2. Add activated carbon nanotubes and thionyl chloride into a reaction kettle and stir. Raise the temperature of the reaction kettle to 60-70° C. and keep the temperature for 18-20 hours. Post-treat to obtain modified carbon nanotubes.

2. The method for preparing the organic-inorganic hybrid phase change energy storage material according to claim 1, characterized in that: In step S1, the usage ratio of the polyethylene glycol, tridecanedioic acid, toluene and catalyst is 10 g: 1-2 g: 150 mL: 0.1-0.5 g, the polyethylene glycol is polyethylene glycol 6000, and the catalyst is titanium n-butoxide; In step S2, the diluent is a 0.5 mol / L tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8.5, and the amount ratio of the modified polyethylene glycol, the diluent, the active carrier and dopamine hydrochloride is 5 g:40 mL:13 g:2 g; in step S3, the amount ratio of the emulsion, the load carrier, the paraffin solution, the modified chitosan dispersion and o-phthalaldehyde is 20 mL:5 g:10 g:10 mL:0.5 g.

3. The method for preparing the organic-inorganic hybrid phase change energy storage material according to claim 1, characterized in that: In step S3, the preparation method of the emulsion is: adding petroleum ether, purified water and dispersant into a reactor and stirring to obtain an emulsion, wherein the amount ratio of the petroleum ether, purified water and dispersant is 5mL:3mL:0.1g, the dispersant is composed of sodium stearate and sodium dodecyl sulfate in a weight ratio of 2:1, and the boiling range of the petroleum ether is 90-120°C.

4. The method for preparing the organic-inorganic hybrid phase change energy storage material according to claim 1, characterized in that: In step S3, the paraffin solution is prepared by adding paraffin and petroleum ether in a dosage ratio of 1 g: 5-7 mL into a reaction kettle, stirring until the system is dissolved, and obtaining a paraffin solution.

5. The method for preparing the organic-inorganic hybrid phase change energy storage material according to claim 1, characterized in that: In step B1, the amount ratio of chitosan, N,N-dimethylformamide and modified carbon nanotubes is 10g:100mL:3-5g, and the deacetylation degree of chitosan is 80-90%; in step B2, the amount ratio of modified chitosan, sodium dodecyl sulfate, purified water and glacial acetic acid is 2g:0.1g:15mL:0.5g.

6. The method for preparing the organic-inorganic hybrid phase change energy storage material according to claim 1, characterized in that: In step C1, the amount ratio of the multi-walled carbon nanotubes to the activation solution is 1g:5-6mL, and the activation solution is composed of 80-90wt% sulfuric acid and 70-80wt% nitric acid in a volume ratio of 2:1; in step C2, the amount ratio of the activated carbon nanotubes to thionyl chloride is 1g:4-6mL.

Citation Information

Patent Citations

  • Preparation method of carbon nanotube modified composite microcapsule

    CN104069783A

  • Preparation method of stabilizer phase change material using sawdust as supporting material

    CN105602529A